1985
DOI: 10.1002/hep.1840050311
|View full text |Cite
|
Sign up to set email alerts
|

Sinusoidal caliber in alcoholic and nonalcoholic liver disease: Diagnostic and pathogenic implications

Abstract: Portal hypertension in alcoholic liver disease has been attributed to an increased resistance to blood flow either of sinusoidal or of postsinusoidal origin. The former should be accompanied by sinusoidal compression while the latter is expected to result in an increased or a normal sinusoidal diameter. Patients with alcoholic liver disease showed a marked reduction (p less than 0.001) in relative sinusoidal area (995 +/- 135 micron 2; n = 19) when compared to nonalcoholic patients with normal liver histology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(19 citation statements)
references
References 20 publications
2
16
0
1
Order By: Relevance
“…Intracellular volume increases can also result in an increase in intrahepatic pressure (13). Studies have shown that an increase in hepatocyte surface area is associated with a reduction in the relative liver sinusoidal area and an increase in portal pressure (14). It has also been demonstrated that hepatocyte size correlates well with hepatic wedge pressures and intrahepatic pressures, which are independent of fatty liver or cirrhosis (13).…”
Section: Introductionmentioning
confidence: 97%
“…Intracellular volume increases can also result in an increase in intrahepatic pressure (13). Studies have shown that an increase in hepatocyte surface area is associated with a reduction in the relative liver sinusoidal area and an increase in portal pressure (14). It has also been demonstrated that hepatocyte size correlates well with hepatic wedge pressures and intrahepatic pressures, which are independent of fatty liver or cirrhosis (13).…”
Section: Introductionmentioning
confidence: 97%
“…The present study showed that alcoholic compensated cirrhotic patients can develop severe portal hypertension even with a relatively well-maintained liver pressure and portal hypertension depending on several conditions which vary from hepatitis virus-related CLDs, such as compression of the hepatic sinusoid by enlarged hepatocytes in the form of ballooning [6][7][8] . In addition, perivenular fibrosis, one of histological characteristics of ALD, is also suggested to contribute to the development of portal hypertension [15][16][17] .…”
Section: Applicationsmentioning
confidence: 65%
“…For instance, the enlargement of hepatocytes with ballooning was reported to mechanically compress the sinusoid and contribute to increased pressure of the portal vein [6][7][8] . Therefore, the severity of portal hypertension in alcoholic liver cirrhosis tends to be more remarkable than that in hepatitis virus-related cirrhosis, and patients with alcoholic liver cirrhosis are suggested to develop large varices even with a relatively well-maintained liver function and general clinical conditions [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…More significant however, are the variable factors which modulate the intrahepatic vascular resistance 10 . Portal flow may be obstructed by compression of simusoids by swollen hepatocytes in alcoholics—even before frank cirrhosis appears 11 …”
Section: Hemodynamics In Portal Hypertensionmentioning
confidence: 99%